2001
DOI: 10.1053/ejvs.2001.1347
|View full text |Cite
|
Sign up to set email alerts
|

Incompetent Perforating Veins are Associated with Recurrent Varicose Veins

Abstract: patients with recurrent varicose veins have both a higher prevalence and a greater number of incompetent perforating veins than patients with primary varicose veins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
46
0
3

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 13 publications
2
46
0
3
Order By: Relevance
“…DVI is rarely the primary cause. The correlation between the occurrence of insufficiency of GSV and PVs has been revealed [6,[14][15][16][17]. In many studies and our study, PVI was found to be most frequently associated with insufficiency in deep veins, GSV, SSV, anterior/posterior accessory GSV, and chronic DVT.…”
Section: Discussionsupporting
confidence: 60%
“…DVI is rarely the primary cause. The correlation between the occurrence of insufficiency of GSV and PVs has been revealed [6,[14][15][16][17]. In many studies and our study, PVI was found to be most frequently associated with insufficiency in deep veins, GSV, SSV, anterior/posterior accessory GSV, and chronic DVT.…”
Section: Discussionsupporting
confidence: 60%
“…It has been suggested that up to 80% of IPVs become competent after standard varicose vein surgery, 9 but IPVs are thought to be the cause of recurrence in up to 50% of legs. [10][11][12] They are also more commonly seen in patients with recurrent than primary varicose veins 13,14 and in limbs with primary varicose veins than in those with no varicose veins. 8 Although IPVs are often seen in patients with deep and superficial insufficiency, the hemodynamic influence of IPVs and clinical benefit attributable to interruption of IPVs have been controversial, but the presence of IPVs after ablation of the GSV has been defined as a major risk factor for nonhealing and recurrent leg ulcers in patients with severe chronic venous disease (CEAP classification C4-C6) and for recurrent varicosities in patients with mild to moderate chronic venous disease (CEAP classification C1-C3).…”
Section: Discussionmentioning
confidence: 99%
“…3. По 3 перфорантным венам (диаметр менее 3,5 мм) сохранился двунаправленный поток, но время рефлюкса было от 0,3 до 0,5 с. В ряде исследований только рефлюкс до 0,3 с по перфорантным венам считается физиологичным [16], поэтому можно ли считать, что они полноценно восстановили свою функцию, остается неясным.…”
Section: локализация несостоятельных перфорантных вен голени выявленunclassified
“…В то же время, в литературе встречаются немного работ по результатам флебэктомии без лигирования перфорантных вен [3,9], больше уделяется внимание миниинвазивным способам устранения поверхностного и горизонтального рефлюксов [2,5]. А практические хирурги очень настороженно относятся к данному подходу [14,16,18].…”
unclassified